Synthesis and length dependent photoluminescence property of zinc oxide nanorods - Ishaq Musa; Naser Qamhieh; Saleh Thaker Mahmoud (Results in Physics, 2017)
One-dimensional nanostructure ZnO nanorods (NRs) with controlled lengths and diameters were synthesized by the growth of colloidal nanoparticles and then characterized by XRD, TEM, Raman, PL and UV–Vis. The growth time parameter plays an important role in the formation process of ZnO NRs. The as-prepared nanoparticles has spherical shape with size about 4 nm, and formed single-crystalline NRs of length up to 150 nm and 16–20 nm in diameters. Raman spectra of the as-grown ZnO nanorods revealed the existence of Raman silent modes B1(low) and B1(high) at 273 and 538 cm−1 respectively. Photoluminescence (PL) and UV–visible absorption measurements have been performed at room temperature. The PL spectrum showed that the relative intensity of ultraviolet (UV) and defect bands depend on the length of ZnO nanorods. The peak of photoluminescence of UV band around 395 nm is strongly enhanced when the length of ZnO nanorods is reduced and the humps around 580 nm decreases. Keywords: ZnO nanorods, Raman spectroscopy, UV–Vis spectroscopy, Photoluminescence spectroscopy